2021
DOI: 10.1093/ndt/gfab030
|View full text |Cite
|
Sign up to set email alerts
|

Tubulointerstitial nephritis and uveitis syndrome: a systematic review

Abstract: Background Tubulointerstitial nephritis and uveitis (TINU) is defined as the occurrence of tubulointerstitial nephritis and uveitis in the absence of other systemic diseases. The most comprehensive review on this condition was published in 2001. Methods We conducted a systematic review of the literature on cases of TINU syndrome. Medline an EMBASE databases were screened. Full-length articles or letters reporting cases with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 180 publications
5
20
1
7
Order By: Relevance
“…The renal prognosis of TINU syndrome is usually described as favorable: recent data from Hayashi et al showed a good renal outcome in a series of 29 children 11 . The same conclusion was drawn from data collected recently by Regusci et al in a systematic review of the literature 12 . Nevertheless, recent studies have highlighted that 70 to 96% of adult TINU patients have chronic kidney failure on long-term follow-up 13,14 .…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The renal prognosis of TINU syndrome is usually described as favorable: recent data from Hayashi et al showed a good renal outcome in a series of 29 children 11 . The same conclusion was drawn from data collected recently by Regusci et al in a systematic review of the literature 12 . Nevertheless, recent studies have highlighted that 70 to 96% of adult TINU patients have chronic kidney failure on long-term follow-up 13,14 .…”
Section: Introductionsupporting
confidence: 80%
“…We showed that children with TINU syndrome may have a poor renal prognosis. Although TINU syndrome is usually described as having a favorable renal outcome 2,12,13,22 , several recent studies suggest that a full kidney recovery is not always achieved especially in adult patients. Indeed, Legendre et al reported that two-thirds of their patients (24/35) had abnormal kidney function (eGFR <90 mL/min/1.73m²) at 1 year of follow-up 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common trigger of AIN is the drug used (46), therefore the identification of the types of drug is important in determining a preventive strategy. Although our results provide new insights of ICPI-and PPI-induced nephritis, further basic and clinical studies are required to elucidate the mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathophysiology remains unclear to date; however, TINU is believed to be triggered by infection or with the use of certain medications (antibiotics or nonsteroidal anti-inflammatory drugs) [2]. This syndrome is reported to have a female predominance (65% of cases) and a median age of 17 [3]. It is reported that TINU is responsible for 5% of the cases of acute tubulointerstitial nephritis [4].…”
Section: Introductionmentioning
confidence: 99%